A STUDY ON THE FOOD AND FEEDING HABITS OF THE MAHSEER TOR TOR (HAMILTON) - Gupta, M Das (Indian Journal of Fisheries, 2011)
The food and feeding habits of the mahsecr Tor tor (Hamilton) has been studied. Tlie species was foundto be an omnivour as evident from gut content analysis and R. L. G. value. It can be considered as voraciousfeeder subsisting mainly on algae and vegetable matter. The feeding intensity increased withthe increasing length of the fish. The food habit of the fish changed from cami - omnivorous to herbi- omnivorous which is also evident from the increasing K. L. G. value increasing with the length of thefish